2018
DOI: 10.3390/molecules23040746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antifungal Activity of Novel Benzo[4,5]imidazo[1,2-d][1,2,4]triazine Derivatives

Abstract: A series of novel fused heterocyclic compounds bearing benzo[4,5]imidazo[1,2-d][1,2,4]triazine 4a–4w were designed and conveniently synthesized via the intermediates 2-(halogenated alkyl)-1H-benzo[d]imidazoles 2a, 2b, and 2-((1-(substituted phenyl)hydrazinyl)alkyl)-1H-benzo[d]imidazoles 3a–3g. The structures of all target compounds were characterized by FT-IR, 1H NMR, 13C NMR, and EI-MS, of which, the structure of compound 4n was further determined by the single crystal X-ray diffraction. The crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The plant pathogenic fungi Fg, Rs, and Bc, which are stored in the Laboratory of Plant Disease Control at Nanjing Agricultural University, were selected to test the antifungal effects of title compounds. Antifungal effects of the target compounds 4a – 4q and the positive control (hymexazol) were evaluated at 100 μg/mL by a mycelium growth rate method . Table showed that the title compounds 4h , 4k , 4n , and 4o effectively inhibited the mycelium growth of Fg, with the inhibition rates of 53.8%, 50.9%, 72.3%, and 60.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant pathogenic fungi Fg, Rs, and Bc, which are stored in the Laboratory of Plant Disease Control at Nanjing Agricultural University, were selected to test the antifungal effects of title compounds. Antifungal effects of the target compounds 4a – 4q and the positive control (hymexazol) were evaluated at 100 μg/mL by a mycelium growth rate method . Table showed that the title compounds 4h , 4k , 4n , and 4o effectively inhibited the mycelium growth of Fg, with the inhibition rates of 53.8%, 50.9%, 72.3%, and 60.3%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Phytopathogenic fungi are the most severe agronomic threat that is overwhelmingly difficult to control in agricultural production and seriously prevents the rapid development of agriculture . Under these circumstances, the rational application of agricultural fungicides is regarded as a safeguard measure to fight the epidemics of phytopathogenic fungi . However, the rapid emergence of fungal resistances and the negative impacts on the environment and nontarget species, which have been brought by the long‐term usage of traditional fungicides, have becoming a critical restrictive factor of agricultural sustainable development .…”
Section: Introductionmentioning
confidence: 99%
“…These types of infections are generally easy to cure; however, millions of people worldwide contract life-threatening invasive infections that are much harder to diagnose and treat [22]. Development of novel fungicides is a promising approach for controlling fungal diseases and overcoming resistant fungus [23]. Accordingly, over the past decades, efforts have been made around the world to develop highly efficient fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…However, these compounds are rarely used in crop production due to the structural instability or poor control in farmland. Therefore, it is tardy to search highly-effective and eco-friendly agrochemicals for fighting against agricultural pathogenic microorganisms (Qian, Lee & Cao, 2010; Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%